Effects of large strain reverse loading on the strain rate dependence and dynamic strain localization of ductile metallic rods - Zhang, L; Townsend, D (Springer Nature, 2022)
The dynamic necking of ductile metallic rods with large strain reverse loading history has received little attention in the published literature. A novel bespoke real time strain control setup is constructed to apply the reverse loading directly to the specimen gauge section up to a maximum strain level of ± 0.16. 304L stainless steel is used as a model material in this study. The subsequent tensile tests of the reverse loaded specimens are performed from quasi-static to high strain rates of 1000/s, using a Zwick 050 Machine, hydraulic Instron 8854, and a bespoke split Hopkinson tension bar with high speed photography equipment. The initial flow stress of the 304L rods shows similar strain rate dependence, regardless of the reverse loading history. The local strain rate during strain localization increases dramatically and eventually reaches one order of magnitude higher than the nominal strain rate. A higher strain reverse loading significantly influences the development of necking instabilities, with smaller strain to necking inception, higher local stress in the necking zone, and higher local strain rate up to failure. Instead of evaluating the impact energy absorption up to necking, an analysis of the local stress–strain relationship indicates that the reverse loaded 304L shows good impact energy absorption up to failure. This agrees with the ductile fracture surfaces of the 304L materials with reverse loading.